KOLABORASI GURU BK DAN GURU MATA PELAJARAN DALAM MEMBANTU PESERTA DIDIK MEMILIKI MASALAH KESULITAN BELAJAR DI SMP NEGERI 30 PADANG - Sinta Syafridayanti; Rici Kardo; Rahma Wira Nita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the suboptimal collaboration between guidance and counseling teachers (BK) and teachers of the subject of Helping Students in Having Learning Difficulties. The purpose of this study is to describe the collaboration between BK teachers and subject teachers in Helping Students with Learning Difficulties, which is reviewed from: Forms of collaboration, and Challenges of collaboration. This study uses a qualitative approach with descriptive data. The key informants in this study were BK teachers (VAP) and subject teachers (SEM), as well as 2 additional informants, namely student representatives (DP), and homeroom teachers (RD). The data collection technique is carried out through interviews and observations, while the data analysis technique uses the stages of data reduction, data presentation, and conclusion drawn. Based on the results of the research that has been carried out on the collaboration of BK teachers and subject teachers in helping students with learning difficulties at SMP Negeri 30 Padang, it shows that the form of collaboration between BK teachers and subject teachers in helping students with learning difficulties is communication, namely communication including informal and formal communication, providing information to each other and exchanging information, both short discussions after class hours, or via WhatsApp. The challenge of collaboration between BK teachers and subject teachers in helping students with learning difficulties is differences in views, lack of communication and time constraints. Collaboration also has an impact on improving teacher professionalism and the overall quality of the learning environment. BK teachers are expected to help students with learning difficulties. Subject teachers are expected to proactively coordinate with BK teachers and integrate the values of learning difficulties problems in learning. The school is expected to provide facility and training support, as well as students who are active in learning difficulties.